2008
DOI: 10.1074/jbc.m800517200
|View full text |Cite
|
Sign up to set email alerts
|

Foxo3 Is Essential for the Regulation of Ataxia Telangiectasia Mutated and Oxidative Stress-mediated Homeostasis of Hematopoietic Stem Cells

Abstract: Unchecked accumulation of reactive oxygen species (ROS) compromises maintenance of hematopoietic stem cells. Regulation of ROS by the tumor suppressor protein ataxia telangiectasia mutated (ATM) is critical for preserving the hematopoietic stem cell pool. In this study we demonstrate that the Foxo3 member of the Forkhead Box O (FoxO) family of transcription factors is essential for normal ATM expression. In addition, we show that loss of Foxo3 leads to defects in hematopoietic stem cells, and these defects res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
287
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(306 citation statements)
references
References 49 publications
16
287
1
Order By: Relevance
“…FoxO3a-deficient HSCs showed more severe reduction in repopulating capacity upon aging [113]. Another research group reported a similar finding, suggesting that Foxo3 is the main player of the FoxO family in HSCs [114]. Warr et al focused on cell autophagy in HSCs.…”
Section: Transcription Factors Regulating Hscssupporting
confidence: 52%
“…FoxO3a-deficient HSCs showed more severe reduction in repopulating capacity upon aging [113]. Another research group reported a similar finding, suggesting that Foxo3 is the main player of the FoxO family in HSCs [114]. Warr et al focused on cell autophagy in HSCs.…”
Section: Transcription Factors Regulating Hscssupporting
confidence: 52%
“…In adult HSCs and NSCs, FOXO factors cooperate to regulate stem cell selfrenewal and homeostasis. Conditional deletion of FoxO1, FoxO3 and FoxO4 in the adult hematopoietic system, as well as germline deletion of the single FoxO3 gene, trigger a loss in long-term repopulating capacity of HSCs due to enhanced exit from quiescence, increased apoptosis and increased levels of reactive oxygen species (Miyamoto et al, 2007;Tothova and Gilliland 2007;Yalcin et al, 2008). FOXO transcription factors are also necessary for the maintenance of adult NSCs (Paik et al, 2009;Renault et al, 2009).…”
Section: Foxo Transcription Factors In Adult Stem Cells: Integrating mentioning
confidence: 99%
“…The mechanism by which IR induces HSC senescence remains to be elucidated but may be attributable to increased production of ROS because a large body of evidence suggests that ROS plays an important role in mediating the induction of HSC senescence under various pathological conditions (69,112,127,149,167). For example, it was found that ATM -/ -mice exhibit progressive failure of hematopoietic function with aging (69).…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
“…Treatment of FoxOs knockout mice with NAC reversed the defects of HSCs and hematopoietic abnormalities. It appears that FoxO3 is the primary regulator of HSCs because the deletion of FoxO3 alone in mice can recapitulate most of the phenotypes observed in the tripleFoxO knockout mice (112,167). The molecular basis for FoxOs to regulate ROS production in HSCs is mainly attributed to their transcriptional regulation of the expression of superoxide dismutase and catalase (149).…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%